Dalla pianta al paesaggio agrario: il know-how come risorsa territoriale - Navarro, Aurore (Scienze del Territorio, 2018)
Domestic biodiversity, breeds and varieties used in local agriculture, diminished considerably during the second half of the 20th century, partly due to the development of selection technology in agriculture and the homogenisation of agricultural landscapes. Since the first decade of the 21st century, several associations have been created in France in order not only to preserve and enhance domestic biodiversity, but also to build territorial projects. In the field cases described, all located in the Rhône-Alpes region in France, we try to show how these initiatives make vegetal domestic biodiversity become a good to defend not only for its intrinsic value but for its territorial amenities also. Local varieties play an important role in food sovereignty and in the adaptation of local agriculture to climate change. Territorial projects lead to a retrieval of abandoned arable land and to a strengthening of local ties between inhabitants and local associations, as well as between farmers and amateur gardeners. They represent an alternative to a global agriculture, disconnected from territories, which keep farmers in a state of dependence on corporations and research laboratories.